2017
DOI: 10.1007/s11356-017-0868-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of oral cadmium intoxication on levels of different essential trace elements and oxidative stress measures in mice: a response to dose

Abstract: The study evaluated the effect of oral intoxication of cadmium and the possible causes of oxidative stress and its preferential accumulation in different organs as well as sub-sequential effects in mice. Twenty-four Swiss albino male mice were divided into three groups viz., normal control group without cadmium chloride (CdCl), whereas a daily dose of 0.5 and 1.2 mg of CdCl was orally administered for a period of a week to dose group 1 (DG-1) and dose group 2 (DG-2), respectively. A significant increase in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 60 publications
4
13
0
Order By: Relevance
“…Another construal could be that systemic and hepatic VD dyshomeostases are extra distressing processes adding to the complexity of the pathogenesis of Cd‐induced liver injury. In this context, Cd‐intestinal absorption and toxic effects were more severe with VD 3 and Ca 2+ deficiency, and hepatic tissue Ca 2+ levels were diminished with chronic Cd toxicity . The trafficking of Cd across intestinal and renal cellular barriers also coincided with inhibitions of several VD‐dependent Ca 2+ ‐transporting proteins and it was suggested that Cd promoted its gathering by causing enterocytes absorption hindrance and excessive renal excretion of Ca 2+ .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Another construal could be that systemic and hepatic VD dyshomeostases are extra distressing processes adding to the complexity of the pathogenesis of Cd‐induced liver injury. In this context, Cd‐intestinal absorption and toxic effects were more severe with VD 3 and Ca 2+ deficiency, and hepatic tissue Ca 2+ levels were diminished with chronic Cd toxicity . The trafficking of Cd across intestinal and renal cellular barriers also coincided with inhibitions of several VD‐dependent Ca 2+ ‐transporting proteins and it was suggested that Cd promoted its gathering by causing enterocytes absorption hindrance and excessive renal excretion of Ca 2+ .…”
Section: Discussionmentioning
confidence: 99%
“…[6] In this respect, Cd pervaded into the targeted cells through the T-type VDCC [9,11] and concomitantly inhibited the L-type channel [12,13] to block [Ca 2+ ] E influx, [43,44] thus resulted in dose-dependent declines in rodent liver Ca 2+ levels. [35,45] Moreover, Cd provoked marked increment in [Ca 2+ ] C by releasing [Ca 2+ ] I from the ER subsequent to the activation of ITPR1 and RYR1. [46,47] Sustained oscillations in [Ca 2+ ] C may then prompt mitochondrial damage and ROS formation by the CAM-CAMKIIα and/or S100B pathways [10,16,17] that could later initiate cell death by ejecting mitochondrial Cyt_C, which binds Casp-9 to activate the chief executor of apoptosis, Casp-3.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations